X makes nine: a distant ice giant in the solar system. (1st June 2016) - van den Berg, Hugo
Ever since Pluto lost its status as one of the main planets of our solar system and was demoted to just another frozen denizen of the Kuiper belt, we have had to make do with eight, albeit in a pleasing symmetry, with four rocky ones this side of the asteroid belt and four giants on the far side. Now it looks like number nine is back on the slate: the existence of a large planet, about ten times as massive as Earth and hundreds of times more distant from the Sun than Earth itself, has been postulated to explain the curiously bunched-up orbits of several small celestial bodies, far beyond the orbit of Neptune. To date, we have only "proof by simulation" and we are yet to observe this massive planet in the backyard of our solar system by more direct means. However, powerful new telescopes should provide visual evidence within the next few decades.